Pengaruh Persepsi Kenyamanan, Interaksi Sosial, Persepsi Streamer dan Persepsi Utilitas terhadap Live Stream Shopping Intentions - Rizka Fatimah; Jatmiko Jatmiko (Universitas 45 Surabaya, 2024)
Live stream shopping is experiencing unprecedented growth. However, research on live stream shopping is still in its infancy. In addition, there are several previous studies with different results regarding the influence of perceived convenience, social interaction, streamer perception and perceived utility have a positive influence on live stream shopping intentions. Therefore, the purpose of this study is to assess the factors that influence shopping intentions in the context of live streaming and to determine whether perceived convenience, social interaction, streamer perception, and perceived utility have a positive impact on shopping intentions through live streaming. This study adopts a quantitative method, the data used is primary data obtained through the distribution of questionnaires to 115 consumers in the Jabodetabek area. The data was analyzed using multiple linear regression methods with SPSS statistical series 27 software. Based on the test results conducted, this study shows that perceived convenience, social interaction, streamer perceptions and perceived utility have a significant effect on live stream shopping intentions.